2019
DOI: 10.3390/polym11101687
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Surface Patterning as a Fouling Mitigation Strategy in Liquid Filtration: A Review

Abstract: Membrane fouling is seen as the main culprit that hinders the widespread of membrane application in liquid-based filtration. Therefore, fouling management is key for the successful implementation of membrane processes, and it is done across all magnitudes. For optimum operation, membrane developments and surface modifications have largely been reported, including membrane surface patterning. Membrane surface patterning involves structural modification of the membrane surface to induce secondary flow due to edd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 88 publications
(119 reference statements)
1
41
0
Order By: Relevance
“…The results confirm the efficacy of the imprinting technique in forming a surface pattern as reported earlier [23]. It is widely reported that surface corrugation offers improvement for mass transport, reduction in membrane fouling formation, and improved energy consumption [29].…”
Section: Membrane Fabrication and Characterizationsupporting
confidence: 88%
See 2 more Smart Citations
“…The results confirm the efficacy of the imprinting technique in forming a surface pattern as reported earlier [23]. It is widely reported that surface corrugation offers improvement for mass transport, reduction in membrane fouling formation, and improved energy consumption [29].…”
Section: Membrane Fabrication and Characterizationsupporting
confidence: 88%
“…The underlying mechanisms for formation of such structure have been detailed elsewhere [30]. This study focuses only on the mutual effect of surface corrugation and a tilted panel in enhancing hydraulic performance [29]. Nonetheless, it is worth noting that the changes in structural properties due to the imprinting step make it difficult to decouple the sole effect of surface corrugation compounded with other properties on the hydraulic performance [33].…”
Section: Membrane Fabrication and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In membrane fabrication, numerous surface modification techniques such as surface patterning [ 19 , 20 , 21 ], polymer blending [ 17 , 22 , 23 , 24 ], and surface coating [ 25 ] have been applied to enhance the membrane properties in reducing its fouling propensity. The surface coating method is popular to fabricate membranes used in a photocatalytic reactor, in which PDA can act as a medium for binding photocatalyst components that otherwise cannot be deposited directly on the membrane surface [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative to coatings and surface treatments, membrane surface patterning has recently attracted attention [18,19]. Tailoring the topographical surface of a polymer membrane can theoretically increase the effective surface area, which is directly proportional to the permeate flux.…”
Section: Introductionmentioning
confidence: 99%